Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Bangun Datar Menggunakan Model PBL Berbantuan Media PPT Interaktif di Kelas III SDN 20 Berok Gunung Pangilun Kota Padang - Adilla, Fitri; Ahmad, Syafri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the improvement in learning outcomes of students in learning flat shapes using the PBL Model Assisted by Interactive PPT Media in Class III SDN 20 Berok Gunung Pangilun, Padang City.This type of research is classroom action research (CAR) with a qualitative and quantitative approach. Implemented in 2 cycles, cycle I consists of two meetings, and cycle II consists of one meeting. Each cycle consists of the planning, implementation, observation, and reflection stages. The subjects of this study were teachers and 25 class III students of SDN 20 Berok Gunung Pangilun. The research data were obtained from the assessment of the learning implementation plan, implementation process and learning outcomes. The data collection techniques used were observation, tests and non-tests. The results of the study in cycle I on the teaching module aspect obtained an average of 85.3% (C) increasing in cycle II to 95.83% (A). The implementation of cycle I on the aspect of teacher activity obtained an average of 82.1% (C) and increased in cycle II to 96.4% (A). The implementation of cycle I on the aspect of student activity obtained an average of 82.1% (C) and increased in cycle II to 96.4% (A). The learning outcomes of students in cycle I obtained an average of 77.07 (C), increasing in cycle II to 87.74 (B). It can be concluded that the Problem Based Learning (PBL) model assisted by Interactive PPT media can improve learning outcomes in learning flat shapes.